Is Helicobacter pylori associated hypergastrinaemia due to the bacterium's urease activity or the antral gastritis?. Issue 11 (November 1991) - Chittajallu, R S; Dorrian, C A; Neithercut, W D; Dahill, S; McColl, K E
Abstract : Eradication of Helicobacter pylori is associated with a fall in serum gastrin but the way in which the infection raises the serum gastrin concentration is not clear. It may be related to the ammonia produced by the bacterium's urease stimulating gastrin release by the antral G cells. Alternatively, the antral gastritis induced by the infection may modify the regulation of gastrin release. We have examined serum gastrin in 10 patients before and 24 hours after starting triple anti-H pylori treatment consisting of tripotassium dicitrato bismuthate 120 mg four times daily, metronidazole 400 mg three times daily, and amoxycillin 500 mg three times daily. The urease activity, assessed by the 20 minute value of the 14C-urea breath test, fell from a median of 176 (range 116-504) kg% dose/mmol CO2 x 100 pretreatment to 5 (2-15) at 24 hours (p less than 0.005). The median antral gastritis score was 6 (4-6) pretreatment and fell to 3 (2-5) at 24 hours (p less than 0.02), and this was due to resolution of the polymorphonuclear component. Despite this complete suppression of bacterial urease activity and partial resolution of antral gastritis the median basal gastrin concentration remained unchanged, being 57 ng/l (45-77) pretreatment and 59 ng/l (45-80) at 24 hours and the median integrated gastrin response to a standardised meal was also unaltered, being 4265 ng/l/min (range 1975-8350) and 4272 ng/l/min (range 2075-6495) respectively. These findings do not support a causal association between H pylori urease activity and hypergastrinaemia and show rapid improvement of antral gastritis after starting anti-H pylori treatment.